WEB APPLICATIONS ONLINE DISTRO FREE UP YOUR STYLE USING MACROMEDIA FLASH 8.0 - Inez Arieza Sinaga; Marzuki, Skom, MMSI Marzuki, Skom, MMSI (Jurnal Sistem Informasi, 2010)
In this modern age, Internet usage is an advanced telecommunications infrastructure,where its use can be done anywhere without knowing where the boundaries, spaceand convenience time.Because there for everyone to visit the site on the internet then construct an onlinesales application that makes it easy distro distro fans want to buy the productdistributions as t-shirts, shirts, jeans, and jackets with a choice of designs and colorsthat can be determined according to personal taste without having to spend lots oftime and cost.Website Creation Application Online Distro Free Up Your Style is using MacromediaFlash 8.